2018
DOI: 10.1002/tafs.10126
|View full text |Cite
|
Sign up to set email alerts
|

River Reach Restored by Dam Removal Offers Suitable Spawning Habitat for Endangered Shortnose Sturgeon

Abstract: The lowermost dam on the Penobscot River, Maine, was removed in 2013, making new habitat available for migratory fish. There is no evidence that endangered Shortnose Sturgeon Acipenser brevirostrum have spawned in the Penobscot River in recent years, but dam removal has facilitated access to potential freshwater habitat essential for spawning. Spawning success also depends on the quality of the available habitat. We sought to describe the distribution and amount of suitable spawning habitat in the first 5-km r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Decades later migratory fish have returned to that river, in the millions for some species (Wippelhauser, 2021). Within the Penobscot River, dam removals have allowed the full suite of native fishes to recolonize parts of their historic ranges (Trinko Lake et al, 2012;Hogg et al, 2013;Izzo et al, 2016;Johnston et al, 2019;Whittum et al, 2023), with populations of some species also numbering in the millions now. The Penobscot River remains heavily impounded and ecological processes are impaired, but rehabilitation has brought a suite of migratory fish back to waters that been without them for generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decades later migratory fish have returned to that river, in the millions for some species (Wippelhauser, 2021). Within the Penobscot River, dam removals have allowed the full suite of native fishes to recolonize parts of their historic ranges (Trinko Lake et al, 2012;Hogg et al, 2013;Izzo et al, 2016;Johnston et al, 2019;Whittum et al, 2023), with populations of some species also numbering in the millions now. The Penobscot River remains heavily impounded and ecological processes are impaired, but rehabilitation has brought a suite of migratory fish back to waters that been without them for generations.…”
Section: Discussionmentioning
confidence: 99%
“…From a combination of passage improvements and adult stocking into spawning lakes, the 2023 river herring run has approached 6 million individuals, increased from tens of thousands of fish before dam removals (DMR, 2022; Figure 3). Shortnose sturgeon have been tracked moving upstream of the former Veazie Dam (Johnston et al, 2019) and several have been encountered at the Milford Dam fish lift. Atlantic salmon permeability through the region with the two dam remnants was greatly improved from critically poor passage (Holbrook et al, 2009) to that of an open river (Izzo et al, 2016).…”
Section: First: Impaired Access To Habitatmentioning
confidence: 99%
“…CR Environmental (2008) considered their volume estimates conservative because: (a) they assumed that 5–10% of the substrate located within about 3 m of the impoundment shorelines (areas not accessible with the survey vessel) was sand and small gravel; (b) they estimated a quantity of interstitial sand and small gravel, based on the frequency of video observations of these substrates at ground truth stations, and assumed all of it would be mobile despite the likelihood that its mobility would depend on the mobility of the cobble matrix in which it was embedded (Lisle & Hilton, 1999); (c) they conservatively assumed thicknesses for the mapped and assumed areas of sand and small gravel based on sub‐bottom sonar profiles, steel probe refusal samples, and/or qualitative video observations; and (d) the estimated post‐removal flow velocity used to identify the 20 mm threshold likely occurs only in the main channel, but many of the mapped and assumed deposits below this threshold were in the littoral zones where velocities are lower. These assumptions, together with results from a recent habitat study of the Veazie reach that found sediment transport capacity there did not change substantially from pre‐ to post‐removal (Johnston, Zydlewski, Smith, Zydlewski, & Kinnison, 2019), suggest the combined volume of mobilized sediment was more likely closer to 15,000 m 3 or even smaller.…”
Section: Study Areamentioning
confidence: 91%
“…Breaching the dams to restore riverine habitats in the lower Snake River will also benefi t ecosystem processes, entire biological communities, and increase climate change resilience of anadromous fi shes. Dam breaching has shown success towards recovering migratory fi sh species, notably in the Elwha River, WA (Hess et al 2020 ;Storch et al 2022 ) and Kennebec and Penobscot rivers, ME (Johnston et al 2019 ;Kober 2019 ;Prosek 2020 ;Sharma and Waldman 2021 ;Wippelhauser 2021 ;NRCM 2022 ). Notably, the Penobscot River project was accomplished by a combination of breaching, fi sh passageways, and increased power production for different dams, such that total hydropower production was maintained while restoring diadromous fi sh runs.…”
Section: Statement Of the American Fisheries Society And The Western ...mentioning
confidence: 99%